Lived Experiences of Parents of Children Having Type-I Diabetes Aged 6 to 12 Years - Sapkota, Sabitra (NPRC Journal of Multidisciplinary Research, 2024)
Type I diabetes is chronic illness which change the life styles of parents, children as well as the entire family. Parents faced many challenges such as care, management (insulin administration, diabetic diet, blood glucose monitoring) and treatment cost. Objective of the study is to explore lived experience of parents of children having type I diabetes. A qualitative phenomenological study design was adopted, and total eleven parents (8 mothers and 3 fathers) were selected as participants by using non probability purposive sampling procedure. Data was gathered by using in-depth interview. The huge information was reduced to smaller statements by grouping similar responses to get actual meaning which were coded, categorized and organized to sub themes and themes. Findings revealed that parents had experienced so many ups and downs emotional feelings during the journey of treatment. They experienced nature of type I diabetes like treatment need for the whole of life, hardship during diagnosis process, facing the diabetes complications, financial crisis and need for treatment in emergency situation. The study also revealed that parents felt permanent impact from their child’s previous health condition and disruption of family unit but they were hopeful about their children’s future consequences. They struggled for supporting and caring their children’s lives at all times in the best possible ways. They learnt to live with children having Type-I diabetes. Parents suggested to launch awareness programs to educate school teachers, staffs and health worker for early diagnosis.